Free radicals and antioxidant defences. Review - Montero, María (1996)
In aerobic life, that is to say, in organisms that  use oxygen to obtain energy, there is danger that their antioxidant defences are overcome by prooxidant forces. This situation, called oxidative stress, is the basis of a wide array of physiological aberrations in mammals, including carcinogenesis, cardiovascular diseases, inmune system  diseases, cataracts, brain dysfuntions and, every the aging process. The source of these situations is the oxidative damage in DNA, lipids and proteins by oxyradicals. Against these oxidant species, living beings have developed a series of mechanisms of antioxidant defence, enzimatic and non enzimatic, that are present in both their organisms and in ingested diet. In recent investigations the relation between oxyradicals production and the appearence of degenerative diseases is established, as well as the possibility to use the diet as an antioxidant therapy. A review of these studies is made.